Penerapan Media Audio dalam Pengembangan Sumber dan Media Belajar PAI Didalam Kelas - Arif Rahman Hakim; Arif Rio Kari; Amalia Nur Hanisah; Rini Amelia Siagian; Siti Ardiyanti; Nur Asiah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
In the world of education, there is what is called learning media which is an integral part of the teaching system used in the teaching and learning process to overcome communication barriers in delivering learning materials. As a professional PAI teacher, you must be able to plan and use various learning media available around you in accordance with the desired learning objectives, one of which is by using audio media. Audio media is a media that conveys messages in the form of sound that can be received by the sense of hearing. This research can be categorized as literature research, especially in the realm of library research. This method involves collecting data through the analysis of various literary sources, not limited to books, but also includes documentation materials, magazines, journals, and newspapers. Audio media for teaching is material that contains messages in the form of auditive (vocal cords or voice discs), which can stimulate the thoughts, feelings, attention and willingness of students so that the teaching-learning process occurs. This media is able to display images and background sounds in accordance with the accompaniment of the images displayed in order to build and improve students' reasoning in mastering an event,, very suitable for use in environmental materials with past events such as SKI material, Aqidah Akhlak, Jurisprudence and Al-Quran Hadith. The use of technology can present audio messages and image visualization is the main characteristic of audio-visual media with its use so that learning is more exciting, not boring, and increases student learning outcomes.